Unveiling the Ethical Tapestry of Clinical and Counseling Psychology Research - Ho Thi Thu Hang (ILIN Institute Makassar, 2024)
This comprehensive examination meticulously navigates the intricate landscape of ethical considerations in clinical and counseling psychology research, employing a rigorous methodology that draws upon historical precedents, including notorious ethical lapses exemplified by the Tuskegee syphilis study, the Stanford prison experiment, and the Milgram obedience study. These historical cases serve as cautionary tales, vividly illustrating the dire consequences of neglecting ethical principles. Furthermore, the examination relies on contemporary ethical guidelines promulgated by reputable organizations such as the American Psychological Association (APA), the Australian Counselling Association (ACA), and the British Association for Counselling and Psychotherapy (BACP), which not only underscore the importance of fundamental principles like informed consent, confidentiality, and respect for autonomy but also provide a methodical framework for shaping ethical research practices. Within this exploration, particular attention is given to the role of Institutional Review Boards (IRBs) as vigilant gatekeepers of ethical integrity. Their meticulous oversight ensures the transparent implementation of informed consent processes and the careful mitigation of potential harm to research participants. This approach prioritizes the safeguarding of human rights and dignity, especially in situations where ethical guidelines intersect with intricate legal and regulatory frameworks. As the field of clinical and counseling psychology continues to evolve, this examination places methodological rigor at the forefront of ethical research endeavors, thereby not only enhancing the field's credibility but also significantly contributing to the well-being of individuals and society at large.